Hurricane Preparation: A Q&A Guide to Water and Food Safety and Quality - Amy H. Simonne; Ronald Schmidt (EDIS)
This document was prepared in response to the questions posted by County Extension FCS faculty in Florida. Consumers in Florida counties frequently asked these questions during the 2004 hurricane season. Answers for each question have been prepared by using resources from UF/IFAS, federal agencies and other reputable sources including Talking About Disaster: Guide for Standard Messages (National Disaster Education Coalition, NDEC, 2004). This is an initial compilation of questions and answers which does not cover every single item related to emergency or hurricane situations. We welcome additional questions from those who use this document. They will be included, along with answers, in the next version of this publication. This document is FCS8789, one of a series of the Family, Youth and Community Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date July 6, 2005.